Homicide concentration and retaliatory homicide near repeats: An examination in a Latin American urban setting. (June 2022) - Chainey, Spencer; Muggah, Robert
Despite numerous attempts to decrease homicides in the Latin American region, high homicide levels have persisted. Examining four cities in Rio de Janeiro, the research reveals the intense geographic concentration of homicides in each city, but illustrates differences in the extent of homicide concentration when using a variety of crime concentration measures. Single events involving multiple homicides and a homicide near repeat pattern are observed, with almost all these incidents taking place in areas of homicide concentration. The findings suggest that programmes targeted to areas of homicide concentration, including interventions that suppress the likelihood of future incidents, could decrease homicides.